Mechanical Properties of Self-Compacting Lightweight Concrete Containing Pumice and Metakaolin - Masoud Dadkhah; Reza Rahgozar; Ali Bandani; Peyman Rahgozar (Journal of Rehabilitation in Civil Engineering)
Self-compacting lightweight concrete (SCLC) is a novel type of concrete that combines the benefits of the lightweight and self-compacting concrete (SCC) types. In this research, the optimal amount of metakaolin used in lightweight concrete containing pumice has been obtained based on the best concrete performance in terms of the greatest simultaneous increase in compressive, tensile and flexural strengths. After choosing the SCLC mixing scheme, L-Box, V-Funnel, Slump flow, and T50 tests were performed to investigate the flowability, passing ability, viscosity, and concrete resistance against segregation. Then, the mechanical properties of SCLC have tested by replacing metakaolin with 0, 5, 10, 15, and 20% by weight of cement. The research results have demonstrated that metakaolin enhances ‎the mechanical strength of SCLC. In addition, by adding metakaolin in the amount of 15% cement weight, the process of improving concrete strength continues. The 28-day SCLC specimens containing 15% metakaolin had compressive, splitting tensile and flexural strength of 26%, 14%, and 11% higher than those of SCLC without metakaolin, respectively. Furthermore, formulas that can ‎predict compressive strength, tensile strength, and ‎flexural strength of 28-day SCLC ‎containing ‎metakaolin have been presented.